Development Concept and Strategy for Creative Tourism of Community-Based Tourism Destinations in Yogyakarta - Ginta Ginting; Ike Janita Dewi; Imas Maesaroh; Maya Maria (Ilomata International Journal of Management, 2023)
The paper explores the current condition and the potential development of creative tourism in the context of community-based tourism (CBT) in Yogyakarta, Indonesia. A particular context was studied, that is, in the times of COVID-19 pandemic, where its adverse effects were experienced by tourism industry. Based on the research of the current state of creative tourism products in the tourism villages as CBT destinations, the paper aims to identify the factors contributing to the development of creative tourism products in tourism villages based on their cultural and natural assets. The research was conducted in three tourism villages in Yogyakarta by employing observation and interviews with the tourism villages’ managers and community members. Data were analyzed employing content-analysis. Findings of the research show that creative tourism is important for the survivability of tourism villages’ business especially during and post pandemic. Findings also bring in the importance of leadership and entrepreneurship of the tourism villages. Such result contributes to the conceptual understanding of creative tourism development, especially in the context of CBT destinations, to be able to enhance the resilience of tourism villages and to continue prosper the local community.